VALUASI MUTU BUNGA POTONG KRISAN YELLOW FIJI MENGGUNAKAN PENGOLAHAN CITRA - Usman Ahmad; Enrico Syaefullah; Hadi K Purwadaria (PERTETA, 2006)
ABSTRACT The domestic and export market of chrysanthemum cut-flower require a prime and consistent cuality. Meanwhile, manual grading system based on human vision resulting in quality inconsistentcy. The objective of this study was to develop computer program for quality evaluation of Yellow Fiji chysanthemum cut-flower using image processing. The cut-flowers were classified into different quality standards (AA,A.B.C) based on the steam length and straightness, and flower diameter. Then results indicated a strong relationship between quality parameters extracted from the image and those obtained from direct meaurement for grade AA,A,B and C with R2=0.98, R2=0.97, R2=0.97, and R2=0.98 respectively for length of stem. Also with R2=0.90, R2=0.87, R2=88, and R2=88 respectively for diamter of flower. The validation of the computer program for the quality evaluation of Yellow Fiji chrysanthemum cut-flower performed a hight a ccuracy of 100% for AA grade, 90% for A grade, 85% for B grade, and 100% for C grade. Keyword: chrysanthemum, image processing, quality evaluation Diterima: 12 Juni 2006; Disetujui: 21 Nopember 2006